PELAYANAN PEKERJA SOSIAL MEDIS BAGI PASIEN YANG MENGALAMI MASALAH BIAYA DI BAGIAN PELAYANAN PASTORAL SOSIAL MEDIS, PELAYANAN KESEHATAN SINT CAROLUS (PKSC) - Hendres Yudayanti, Sr. Theresia Endang (Jurnal Insani, 2014)
The Social Work in hospital is a practice social worker to resolve psychosocial problem of patients related the process of illness healing in hospital. This research will describes the process of social worker services for patients who have problems of cost. This research conducted in health care of Sint Carolus Hospital, Jakarta.The purpose of this study was to know about: (1) Process of social worker services in Sint Carolus Hospital to help resolve social problem of patients especially the problem of cost. (2) The factors that influence the process of social work services in health care of Sint Carolus Hospital. (3) The barriers of social workers services to solve the social problems of patients in Sint Carolus Hospital.The conclution of this research is: (1) The process of social worker services in the field of health care in Sint Carolus Hospital is the steps being taken by social workers in dealing with patients in a professional manner. The stage is following the intervention phase of generalist social work. The problem solving steps include: assessments, identification of problems, set goals, intervention planning, intervention, evaluation and termination. (2) The factors to influence social worker services: organization, social worker, other health profession as well as patient and their family. These factors such as the rules and policies of government agencies, hospitals management , social worker services procedures, Human Resources of social worker and the other professional personnel to responding the social problems of the patient, as well as the patient or the patient's family behavior to addressing their social problems, especially their cost problem. (3) The hindrance of the social worker services process occurs on the client outreach. The involvement of social workers to resolving social problems of patients was too late, and patient was overdue consulted to social worker. Another barrier is the lack of social workers in hospitals and health workers less responsive and did not understanding well about the social problems experienced by the patient as wel as the client is not transparent and passive.